2016
DOI: 10.1017/s0266467416000493
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sedimentary processes on white-sand vegetation in an Amazonian megafan

Abstract: Abstract:Amazonian white-sand vegetation has unique tree communities tolerant to nutrient-poor soils of interest for interpreting processes of adaptation in neotropical forests. Part of this phytophysionomy is confined to Late Quaternary megafan palaeo-landforms, thus we posit that sedimentary disturbance is the main ecological factor controlling tree distribution and structuring in this environment. In this study, we characterize the topographic trend of one megafan palaeo-landform using a digital elevation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
1
9
0
2
Order By: Relevance
“…The megafan paleomorphology constituted an environment favourable to the colonization of grassland and shrubland vegetation, which is in sharp contact with surrounding rainforest. A previous publication also demonstrated that forest patches within the megafan consist of tree communities with a lower number of species, lower canopy height and lower diameter at breast height (DBH) than those from the surrounding rainforest (Cordeiro et al ., ). The megafan deposits are moderately to poorly‐sorted, subrounded to subangular, very fine to coarse‐grained, kaolinized sands locally interbedded with silts and muds of Late Pleistocene–Holocene ages (Rossetti et al ., ) (Figures and ); sands typically have dispersed granules of angular to subangular quartz pebbles.…”
Section: Physiography and Geological Frameworkmentioning
confidence: 97%
See 2 more Smart Citations
“…The megafan paleomorphology constituted an environment favourable to the colonization of grassland and shrubland vegetation, which is in sharp contact with surrounding rainforest. A previous publication also demonstrated that forest patches within the megafan consist of tree communities with a lower number of species, lower canopy height and lower diameter at breast height (DBH) than those from the surrounding rainforest (Cordeiro et al ., ). The megafan deposits are moderately to poorly‐sorted, subrounded to subangular, very fine to coarse‐grained, kaolinized sands locally interbedded with silts and muds of Late Pleistocene–Holocene ages (Rossetti et al ., ) (Figures and ); sands typically have dispersed granules of angular to subangular quartz pebbles.…”
Section: Physiography and Geological Frameworkmentioning
confidence: 97%
“…However, other areas with such phytophysiognomy were related to residual landforms reflecting depositional environments deactivated in a relatively recent geological time (e.g. Rossetti et al ., ; Amaral et al ., ; Rossetti et al ., , ; Cordeiro et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, our analysis also includes adjacent areas of relatively recent (Late Pleistocene-Holocene) or significantly older (Plio-Pleistocene or older) geological history. An earlier publication has shown that the diversity of tree species in the patches of white sand vegetation from this megafan is lower than that in the surrounding rainforest (Cordeiro et al 2016). We unify these data with additional tree plots to better detect floristic differences between forests on the megafan sediments and older basement rocks.…”
Section: Introductionmentioning
confidence: 95%
“…Recent works have demonstrated that the ecosystems which form the mosaic of landscapes in this region present a direct integration between the plant cover and the physical, chemical and biological attributes of the soil [23] due to essential processes related to the biogeochemical cycles, water Table outcrops, accumulation and decomposition of organic matter [16,24]. This is a strong indication that environmental conditions associated with temporal flooding, sediment drag, and nutrient leaching may have high importance in the formatting of different forest types in this peripheral region of the Amazonia [25][26][27].…”
Section: Introductionmentioning
confidence: 99%